2001
DOI: 10.1002/ijc.1485
|View full text |Cite
|
Sign up to set email alerts
|

Molecular disorders in transitionalvs. peripheral zone prostate adenocarcinoma

Abstract: Loss of heterozygosity (LOH) and microsatellite instability (MSI) have been shown to be mechanisms for tumor-suppressor gene inactivation in human oncogenesis. In our study, we examined LOH and MSI using 16 polymorphic markers of DNA for chromosomes 1, 3, 7, 8, 10 and 11. Microdissected tumor samples were isolated from 32 patients, representing 11 foci of incidentally discovered prostate cancer of the transitional zone (TZ), 12 prostate cancer of the peripheral zone (PZ) and 10 of high-grade PIN. We found loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The persistent growth arrest characteristic of clones obtained from the CZ was reversed by inactivation of junB by siRNA transfection. Distinct and specific genetic alterations in different chromosomes have been detected between PZ and TZ carcinomas (22), and basal cells Fig. 4.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The persistent growth arrest characteristic of clones obtained from the CZ was reversed by inactivation of junB by siRNA transfection. Distinct and specific genetic alterations in different chromosomes have been detected between PZ and TZ carcinomas (22), and basal cells Fig. 4.…”
Section: Discussionmentioning
confidence: 98%
“…Most predominant and aggressive cancers occur in the PZ, with less aggressive cancers and benign prostatic hyperplasia occurring exclusively in the TZ and much less in the CZ. This suggests different molecular mechanisms based on distinct and specific genetic alterations (22,23). Therefore, examination of TAC derived from the biologically different zones may give insights into the mechanisms underlying prostate carcinogenesis.…”
mentioning
confidence: 99%
“…This damaged DNA can accumulate and eventually lead to the development of neoplasms, such as hereditary nonpolyposis colon cancer (HNPCC), which is characterized by mutations in five microsatellites [3]. A number of studies have reported more MSI in PC tumor tissue compared to normal prostatic tissue [4-9], but some PC tissue studies have found a low frequency of MSI [10-14]. In addition, reduction or loss of MMR protein expression has been found in human PC cell lines, such as LNCaP, PC-3 and DU145 [15-20].…”
Section: Introductionmentioning
confidence: 99%
“…The above MMR phenotype may be linked to early development of transitional zone PC. 289 Wille et al 290 evaluated MSI as a marker to estimate the cancer risk in PC families. They studied seven first-degree relatives of PC probands and found 28% tumour MSI, suggesting that MSI is not more common when two first-degree relatives have PC than in sporadic PC.…”
Section: Mismatch Repair Genesmentioning
confidence: 99%